Pengembangan Media Pembelajaran IPAS Berbasis Mystery box untuk Meningkatkan Hasil Belajar Murid Kelas IV SD - Vinardita Meganesia; Desi Wulandari (Journal of Classroom Action Research, 2026)
This research aims to develop and test the feasibility and effectiveness of Mystery box learning media for substance form materials and their changes in grade IV elementary school students. The research uses the Research and Development model with ADDIE (Analysis, Design, Development, Implementation, Evaluation) stages. Preliminary analysis showed that social studies learning was still dominated by lectures, passive students, and low learning outcomes. The Media Mystery box is designed to be concrete, innovative, and interesting, containing practicum activities, educational games, and visual diagrams. Validation by material and media experts showed that the media was very feasible to use with a feasibility percentage of 94.23% and 95.83%, respectively. Small-scale (7 students) and large-scale (22 students) trials showed a significant improvement in learning outcomes, with an N-Gain value of 0.6126 (medium category). The teacher and student response questionnaire showed a very high positive response, with a percentage of teacher responses of 100% and student responses of 98.57%. The results of the study showed that the Mystery box media was effective in increasing students' understanding of concepts, motivation, and involvement in learning science. This media provides a concrete learning experience that supports the understanding of abstract material in an interactive and fun way.